Interaksi dan Daya Predasi Larva Menochilus sexmaculatus Fabr. terhadap Aphis gossypii Glover di Area Pre Nursery Elaeis guineensis Jacq. - Jojon Soesatrijo (JURNAL CITRA WIDYA EDUKASI, 2022)
Larvae of Menochilus sexmaculatus Fabr. has an important role in the aspect of biological control by using natural enemies (predators) in a sustainable and sustainable manner. This study aims to determine the interaction and predation of the larvae of Menochilus sexmaculatus Fabr. against Aphis gossypii Glover in the pre-nursery area of ??Elaeis guineensis Jacq. at the nursery stage of oil palm plantations. This research was conducted in an oil palm nursery area of ??Karapyak village, Cintamekar Serangpanjang, Subang, West Java. This research is an exploratory research conducted in February – March 2022. The results of the study indicate that Menochilus sexmaculatus Fabr. has the potential to be used as a biological agent. Menochilus sexmaculatus Fabr. has a life cycle that can be adapted in oil palm plantation areas, especially nursery areas. During the 15 minute observation period a larva of Menochilus sexmaculatus Fabr. on average the most capable of preying on the nymph stage of Aphis gossypii Glover as many as 8.4 tails. This was followed by 4 wingless imago stages, 2.2 egg stages and 0.8 winged imago stages. Utilization of natural enemies of the larvae of Menochilus sexmaculatus Fabr. Aphis gossypii Glover is very important to support the success of environmentally sound and sustainable plant pest control in oil palm nurseries.